A CASE OF ECTOPIC CUSHING’S SYNDROME FROM AN OCCULT SOURCE IN A PATIENT WITH DIABETES, HYPERTENSION AND ACUTE PSYCHOSIS: THE DILEMMA IN PLANNING A CURE - Joshi, Nidhi; Joshi, Harish (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND A 40-year-old patient with diabetes and hypertension, prior alcohol use and psychotic episodes, presented with accelerated hypertension associated with agitation and erratic behavior. Biochemical assessment revealed normal renal and hepatic function, elevated hepatic enzymes, spontaneous hypokalemia, poor glycemic control and central hypothyroidism. In view of the patient’s facial plethora, obesity, subtle striae and subtle pigmentation of periungual areas, Cushing’s syndrome was considered. The baseline cortisol was significantly elevated while the adrenocorticotropic hormone (ACTH) was in the low-normal range. A two- day high-dose dexamethasone suppression test (HDDST) showed around 50% suppression. Imaging studies revealed a normal pituitary structure on MRI and bilaterally enlarged adrenal glands on adrenal CT. Inferior Petrosal Sinus Sampling (IPSS) revealed no gradient. The chest imaging did not reveal any suspicious nodules. Hence, we considered the patient to have an Ectopic Cushing’s syndrome with an occult source. Medical therapy using ketoconazole was deferred in view of the elevated hepatic enzymes and psychological status. Following an educated decision with the family, bilateral adrenalectomy was done. The patient had an uneventful post-operative status with improvement of hyperglycemia, hypertension and behavior. Routine adrenal hormone replacement, anti-hyperglycemic and anti-hypertension therapies were continued with no untoward consequences. CONCLUSION In cases of clinically symptomatic ectopic Cushing’s syndrome where the source remains occult despite expeditious work-up, aggressive management through bilateral adrenalectomy is a beneficial therapeutic option to selected patients such as in this case.